Fungsi filsafat ilmu dalam pengembangan metode ilmiah - Sari, Rifa Nita (Maliki Interdisciplinary Journal, 2025)
Philosophy of science has a very significant role in the development of scientific methods. As a theoretical foundation, philosophy of science helps provide logical, ethical, and methodological guidelines for the scientific process. This research aims to explain the contribution of philosophy of science in the development of scientific methods. The main library sources used as references are journal articles which are used as material for analysis. The results of this research show that the philosophy of science has a great influence on the development of the scientific method. The philosophy of science provides a theoretical, logical and ethical foundation for the scientific method. Philosophy of science helps answer fundamental questions, guides the application of the scientific method, and critiques its limitations. In contrast, the scientific method provides practical application of the principles developed in the philosophy of science. The two work together to expand human understanding of the world.